The Ebola Disinfection Booth: Evaluation of an Enclosed Ultraviolet Light Booth for Disinfection of Contaminated Personal Protective Equipment Prior to Removal. (20th July 2015) - Tomas, Myreen E.; Cadnum, Jennifer L.; Jencson, Annette; Donskey, Curtis J.
Abstract : A portable booth designed to disinfect full-body coverage protective equipment before removal using ultraviolet-C radiation resulted in at least 3 log reductions in bacteriophage MS2 and methicillin-resistant Staphylococcus aureus within 3 minutes. The booth could be useful for disinfection of contaminated protective equipment before removal during care of Ebola patients. Infect Control Hosp Epidemiol 2015;36(10):1226–1228